A Systematic Review and Meta-Analysis of the Data Behind Current Recommendations for Corticosteroids in Non–HIV-Related PCP: Knowing When You Are on Shaky Foundations - Injean, Patil (Transplant Direct, 2017)
BACKGROUND: Randomized trials show a mortality benefit to adjunctive corticosteroids for human immunodeficiency virus (HIV)-related Pneumocystis jiroveci pneumonia (HIV-PCP). Guidelines for non-HIV PCP (NH-PCP) recommend adjunctive corticosteroids based on expert opinion. We conducted a systematic review and meta-analysis characterizing adjunctive corticosteroids for NH-PCP. METHODS: We searched MEDLINE from 1966 through 2015. Data on clinical outcomes from NH-PCP were extracted with a standardized instrument. Heterogeneity was assessed with the I(2) index. Pooled odds ratios and 95% confidence interval were calculated using a fixed effects model. RESULTS: Our search yielded 5044 abstracts, 277 articles were chosen for full review, and 6 articles described outcomes in moderate to severe NH-PCP. Studies were limited by variable definitions, treatment selection bias, concomitant infections and small sample size. Individual studies reported shorter intensive care unit stay and duration of mechanical ventilation of patients given adjunctive corticosteroids. There was no association between corticosteroids and survival in NH-PCP (odds ratio, 0.66; 95% confidence interval, 0.38-1.15; P = 0.14). CONCLUSIONS: The literature does not support an association between adjunctive corticosteroids and survival from NH-PCP but data are limited and findings should not be considered conclusive. Further research with improved methodology is needed to better understand the role of adjunctive corticosteroids for NH-PCP.